PALEOGEOGRAPHIC EVOLUTION OF THE ADRIATIC AREA SINCE OLIGOCENE TO PLEISTOCENE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The paleogeographic evolution of the Apulo—Dalmatic Realm, since Oligocene to Pleistocene, has been reconsidered according to the geology of the South Adriatic area and the characters of the mammalian continental faunas of the Gargano Peninsula.
Keywords: Apulo-Dalmatic Realm; Paleogeography; Biostratigraphy; Mammal faunas; Neogene; Pleistocene.